Geology and Land Suitability Analysis for Final Processing Waste Site in Ambon Island - Mailoa, Winardcova Vania Cerwyn; Kololu, Micky; Ulfa, Yuniarti; Puradimadja, Deni Juanda (EKSPLORIUM, 2024)
From 2017 to 2021, waste production in Ambon City increased from 200 tons/day to 297 tons/day, but the condition of the Toisapu landfill in Ambon did not support this. Toisapu landfill, which has been operating since 2007, is now in overload status and needs to be re-evaluated because it is on a slope of >20% and is located close to residential areas. This research aims to find an alternative replacement for the Toisapu landfill with the status of a Waste Processing and Final Processing Site that complies with Indonesian National Standards. This research uses an environmental geology approach based on Spatial Multi-Criteria Evaluation (SMCE), which combines geological and non-geological parameters. The analysis results for each parameter are overlaid, given a value, and then totaled to produce the most feasible land. The results of this research show that the most suitable land is in Wakal with an area of 126,668 ha. The permeability of this location is low, with the groundwater being quite deep (>80 meters), so there is little chance of leachate seepage contaminating the groundwater. In contrast to the Toisapu landfill, Wakal has a slope of <20%, far from protected forests and where residents live.